National Happiness and Genetic Distance: A Cautious Exploration - Eugenio Proto; Andrew J. Oswald (Institute for the Study of Labor (IZA), 2014)
This paper examines a famous puzzle in social science. Why do some nations report such high happiness? Denmark, for instance, regularly tops the league table of rich nations' well-being; Great Britain and the US enter further down; France and Italy do relatively poorly. Yet the explanation for this ranking - one that holds even after adjustment for GDP and socio-economic and cultural variables - remains unknown. We explore a new avenue. Using data on 131 countries, we document a range of evidence consistent with the hypothesis that certain nations may have a genetic advantage in well-being.
Keywords: I30; I31; 330; well-being; international; happiness; genes; GDP